2007
DOI: 10.1159/000107969
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Evacuatory Function due to Specific Smooth Muscle Reactivity in the Gastrointestinal Tracts of Tacrine-Treated Rats

Abstract: Most of the side effects induced by tacrine are associated with the gastrointestinal (GI) tract. The aim of the study was to analyze the nature of radiographically registered, tacrine-induced changes in evacuatory function, as well as to find a possible correlation with the immediate in vitro action of the drug on smooth muscles from the GI tracts of rats. The tacrine dose we used reliably delayed GI passage: contrast matter was not fully evacuated, predominantly from the stomach and cecum. The delay resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that cholinesterase inhibitors stimulate the contractile activity of isolated gastric smooth muscles (SM) [9] and the motility of gastrointestinal (GI) tract [10][11][12] by raising the level of endogenous acetylcholine, which is a main excitatory neurotransmitter for the tract. Tacrine is not an exception to this rule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that cholinesterase inhibitors stimulate the contractile activity of isolated gastric smooth muscles (SM) [9] and the motility of gastrointestinal (GI) tract [10][11][12] by raising the level of endogenous acetylcholine, which is a main excitatory neurotransmitter for the tract. Tacrine is not an exception to this rule.…”
Section: Introductionmentioning
confidence: 99%
“…It is a result from the direct action of tacrine over the contractile apparatus of the gastrointestinal smooth muscles [14]. When applied in vivo (daily dose 0.5 mg/kg) the drug significantly influences the motility of GI tract, causing hypotension, inhibited peristaltic activity and retarded evacuatory kinetics [12,16]. This influence, untypical of acetylcholinesterase inhibitors, indicates a significant presence of non-anticholinesterase mechanisms in the formation of the total drug effect and most likely accounts for its specific side effects on GI tract motility [12,16,17].…”
Section: Introductionmentioning
confidence: 99%